Manajemen Soft Skill Mahasiswa Program Studi Pendidikan Agama Islam: Menumbuhkan Kesadaran Berwirausaha Di Universitas Nahdlatul Ulama Sunan Giri - Siti Khoiriyah; Ahmad Shofiyuddin (LPPM IAIN Sorong, 2024)
Islamic religious education in higher education has an important role in forming student character, including developing soft skills needed in the world of work. Management of student soft skills, especially entrepreneurial awareness, is essential in the current era of globalization. This research reflects the important role of soft skills management in developing independent character, as well as entrepreneurial abilities as the main capital in facing social and economic change. The method used in this research is a qualitative approach through in-depth interviews, observation and document analysis. The research results show that the management of students' soft skills in the Islamic Religious Education study program is implemented through intracurricular activities contained in the course curriculum and academic culture as well as through extracurricular activities which constitute coaching. This realized application has integrated entrepreneurial awareness as an important competency. However, there are still challenges in implementing entrepreneurial practices in the real world.